ChemInform Abstract: Asymmetric Addition of Aryloxy Ethynyl Lithium Derivatives to N‐Sulfinyl Imines. Issue 32 (18th July 2013) - Verrier, Charlie; Carret, Sebastien; Poisson, Jean‐Francois
Abstract Aryloxypropargyl sulfinamides (III) are efficiently obtained, in most cases with high diastereoselectivity.